Strain-free GaN/InAlN chirped short-period superlattice electron-blocking layer for 450 nm InGaN laser diode. (20th March 2019) - Paliwal, Avinash; Singh, Kuldip; Mathew, Manish
Abstract: In this study, we optimized the lattice-matched GaN/In0.18 Al0.82 N chirped short-period superlattice (C-SPSL) electron-blocking layer for a laser diode emitting at 450 nm. The effective bandgap of C-SPSL depends upon the quantum well (QW) and quantum barrier (QB) thickness of C-SPSL. In this study the In0.18 Al0.82 N QB thickness is constant at 0.5112 nm (1 unit layer (UL) = 1 lattice constant thickness) and the GaN QW thickness is varied as 1 UL, 3 UL, and 5 UL. The estimated effective bandgap for 15 periods of 1 UL GaN/1 UL In0.18 Al0.82 N SPSL is 4.2 eV, for four periods of 3 UL GaN/1 UL In0.18 Al0.82 N SPSL it is 3.93 eV and for two periods of 5 UL GaN/1 UL In0.18 Al0.82 N SPSL it is 3.62 eV. Wave-function hybridization and the built-in electric field play an important role in the bandgap behavior of C-SPSL. The electron leakage decreased from 2534.6 A cm −2 to 14 A cm −2 while hole transportation improved from 7.7 kA cm −2 to 10 kA cm −2 at 10 kA cm −2 injection current density. The light output power per facet improved from 146 mW to 255 mW. Slope efficiency increased from 0.548 W A −1 to 0.924 W A −1 with the C-SPSL design.